2010
DOI: 10.1186/1471-2458-10-141
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and metabolic syndrome: a cross sectional survey in adolescents in Ho Chi Minh City, Vietnam

Abstract: BackgroundThe emerging epidemic of overweight/obesity in adolescents in Ho Chi Minh City, Vietnam underlines the importance of studying the metabolic syndrome in Vietnamese adolescents who are becoming progressively more inactive. No study in Vietnam has examined the association of metabolic syndrome with moderate to vigorous physical activity (PA) levels among adolescents. We aimed to examine this association in a sample of urban adolescents from Ho Chi Minh City.MethodsA cross-sectional assessment was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
70
3
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 41 publications
11
70
3
3
Order By: Relevance
“…Specifically in adolescents, some studies have found an inverse association between low levels of physical activity and higher risk of developing MetS [18,19,23,24], however, other studies have not identified any association [11,12,14,16,20,25]. Similarly, sedentary behavior over a long period has been mentioned in some studies as associated with higher chances of developing MetS [14,21,25], while other studies found no association [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in adolescents, some studies have found an inverse association between low levels of physical activity and higher risk of developing MetS [18,19,23,24], however, other studies have not identified any association [11,12,14,16,20,25]. Similarly, sedentary behavior over a long period has been mentioned in some studies as associated with higher chances of developing MetS [14,21,25], while other studies found no association [10,12].…”
Section: Introductionmentioning
confidence: 99%
“…In urban areas men involved in office based desk work could also be involved in low physical activity but in this population of lower sociol economic status they are likely to get involved in work which needs moderate to vigorous activity like manual labourers, paddy workers etc. Excess weight gain and physical inactivity are two important determinants of metabolic syndrome 2. Other potential determinants of metabolic syndrome are age, diet, alcohol, smoking, ethnicity, and so on 3.…”
Section: Introductionmentioning
confidence: 99%
“…Brage et al 2004b;Ekelund et al 2009;Jimenez-Pavon et al 2013b) or null (4/7 studies; Rizzo et al 2007;Schofield et al 2009;Moreira et al 2011;Hjorth et al 2014a). 1/1 studies found that lower mean cadence values were associated with larger accrued numbers of risk factors (Barreira et al 2013) VPA: associations were favourable (1/2 studies; Jimenez-Pavon et al 2013b) or null (1/2 studies; Stabelini Neto et al 2014) MVPA: associations were favourable (6/8 studies; Ekelund et al 2006;Nguyen et al 2010;Carson and Janssen 2011;Holman et al 2011;Jimenez-Pavon et al 2013b;Stabelini Neto et al 2014), null (1/8 studies; Hjorth et al 2014a), or mixed (favourable and null; 1/8 studies; Rey-Lopez et al 2013). 1 study found that the odds of a high cardiometabolic risk score decreased in a graded dose-response manner across quartiles of sporadic MVPA or bout MVPA, with similar associations for some individual cardiometabolic disease risk factors (non-HDL cholesterol, CRP, systolic BP) (Holman et al 2011) Note: The range of mean ages was 5.1 to 17.0 years.…”
Section: Mpamentioning
confidence: 99%
“…m The quality of the evidence from longitudinal studies was downgraded from "low" to "very low" because of serious risk of bias in 3 studies that diminished the level of confidence in the observed effects. n Includes 47 cross-sectional studies (Brage et al 2004a(Brage et al , 2004bGutin et al 2005b;Wennlof et al 2005;Andersen et al 2006;Ekelund et al 2006Ekelund et al , 2009Hurtig-Wennlof et al 2007;Quiros-Tejeira et al 2007;Rizzo et al 2007Rizzo et al , 2008Butte et al 2007b;Ruiz et al 2007;Leary et al 2008;Mark and Janssen 2008;Sardinha et al 2008;Sakuragi et al 2009;Schofield et al 2009;LeBlanc and Janssen 2010;Nguyen et al 2010;Owen et al 2010;Carson and Janssen 2011;Holman et al 2011;Moreira et al 2011;Colley et al 2012;Hay et al 2012;Hearst et al 2012;Henderson et al 2012;Jimenez-Pavon et al 2012, 2013b, 2013cMartinez-Gomez et al 2012;Mota et al 2012;Mendoza et al 2012;Barreira et al 2013;Carson et al 2013;Chaput et al 2013;Janssen et al 2013;Lamotte et al 2013;Knowles et al 2013;…”
Section: Mpamentioning
confidence: 99%